2021
DOI: 10.4308/hjb.28.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Histological Observation of Endophytic Fungi Isolated from Medicinal Plant, Physalis angulata L.

Abstract: Some endophytic fungi species live in medicinal plant tissue and does not make any damage, but live in symbiotic mutualism relationship with the host plant. This research was done to: 1) identify the endophytic fungi species isolated from P. angulata leaf, twig, and stem bark tissues, 2) determine the endophytic fungi colonization in the P. angulata plant tissue by histologic observation. The endophytic fungi was isolated from healthy P. angulata plant parts, then inoculated on Potato Dextrose Agar medium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…C. aenigma have been isolated from Persea americana [12]. C. alienum could be found as one of some endophytic fungi species in Michelia champaca L. [13]; in Physalis angulata L. leaf [14]; in Cananga odorata leaf and flower petal [15]; and Malus domestica plant [12]. C. aotearoa also found as an endophytic fungi species ini Cananga odorata [15].…”
Section: The Identification Results Of Endophytic Fungimentioning
confidence: 99%
“…C. aenigma have been isolated from Persea americana [12]. C. alienum could be found as one of some endophytic fungi species in Michelia champaca L. [13]; in Physalis angulata L. leaf [14]; in Cananga odorata leaf and flower petal [15]; and Malus domestica plant [12]. C. aotearoa also found as an endophytic fungi species ini Cananga odorata [15].…”
Section: The Identification Results Of Endophytic Fungimentioning
confidence: 99%
“…Colletotrichum alienum and Colletotrichum kahawae was also found as endophytic fungi in Cananga odorata, a sort of plant that the flower also used for ritual ceremony as well as J. sambac [6]. Colletotrichum kahawae also found in Cordilyne fratiosa plant [14] and Switenia mahagoni [8] The research about endophytic fungi in Hedychium acuminatum also reported that Colletotrichum alienum and Rhizoctomia sp. Also found in this plant [14] and found in Physalis angulata [7].…”
Section: The Endophytic Fungi Species Isolated From J Sambac Plant Id...mentioning
confidence: 94%
“…Colletotrichum kahawae also found in Cordilyne fratiosa plant [14] and Switenia mahagoni [8] The research about endophytic fungi in Hedychium acuminatum also reported that Colletotrichum alienum and Rhizoctomia sp. Also found in this plant [14] and found in Physalis angulata [7].…”
Section: The Endophytic Fungi Species Isolated From J Sambac Plant Id...mentioning
confidence: 96%
See 1 more Smart Citation